Method for preparing single-layer or few-layer graphene by taking expanded graphite as raw material
Through simplified oxidation process and high-temperature spray pyrolysis technology, single-layer or small-layer graphene is prepared using expanded graphite, which solves the problems of high cost and poor safety in the existing technology, and achieves low-cost and efficient graphene preparation, which promotes the The sustainable development of the lithium-ion battery industry.
Patent Information
- Application Number
- CN202411636572.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing graphene preparation technology has problems such as high cost, long time consumption, poor safety, and difficulty in preparing single or small layers of graphene, and traditional methods have great safety risks to the environment and human body.
Using expanded graphite as raw material, single-layer or small-layer graphene is prepared by simplified oxidation process and high-temperature spray pyrolysis technology. The process flow is simple, reducing the use of chemical reagents, and is suitable for industrial production.
It has achieved low-cost, safe and efficient preparation of single-layer or small-layer graphene, alleviated the pressure on the environment by waste lithium-ion batteries, improved the recycling value of graphite resources, and was suitable for the sustainable development of the lithium-ion battery industry.
Smart Images

Figure CN119191283A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of waste lithium-ion battery recycling, and more specifically, relates to a method for preparing single-layer or few-layer graphene using expanded graphite as a raw material. Background Art
[0002] In recent years, lithium-ion batteries have gradually occupied an important position in consumer electronics, new energy vehicles, and energy storage industries due to their high capacity, high specific energy density, high operating voltage, low self-discharge, good cycle stability, low cost, and environmental friendliness. However, with the explosive growth in the use of lithium-ion batteries, a large number of scrapped lithium-ion batteries will inevitably be generated. If a large number of waste lithium-ion batteries are not properly disposed of, they will cause harm to the environment that cannot be ignored. Graphite is the negative active material of lithium-ion batteries, accounting for about 20% of lithium-ion batteries. It is estimated that by 2025, more than 52 million kg of waste lithium-ion battery negative electrode materials will face recycling. The negative electrode graphite itself is a resource that can be recycled and reused to generate economic value again, but it contains a large amount of harmful electrolytes and heavy metals. If improperly disposed of, it will cause waste of resources and damage to the ecological environment.
[0003] Graphene films with larger areas can be produced by chemical vapor deposition (CVD) and epitaxial growth methods, but these methods are costly, which limits their commercial applications. Currently, the most widely used chemical method is to first oxidize graphite into graphite oxide to increase the interlayer spacing of graphite, then peel off to produce graphene oxide, and finally reduce it to produce high-value product graphene. The main methods of graphite oxidation are: method (a mixed acid of potassium chlorate and concentrated nitric acid as an oxidant), Saudenmaier method (concentrated sulfuric acid and fuming nitric acid as an oxidant) and Hummers method (a mixed solution of concentrated sulfuric acid, sodium nitrate and potassium permanganate as an oxidant), wherein The reaction conditions of the Saudenmaier method are harsh, the oxidation degree of graphite by the Saudenmaier method is insufficient, and the Hummers method has become the main method for preparing graphite oxide because of its high oxidation efficiency and short time consumption. However, a large amount of reducing agent, high temperature and high pressure and other conditions are still required for the subsequent reduction and preparation of graphene.
[0004] At present, there are related reports on the use of Hummers method to regenerate graphene from the negative electrode graphite of waste lithium-ion batteries. CN111384462 A discloses a method for preparing graphene by recovering graphite from the negative electrode materials of waste lithium-ion batteries, wherein the waste lithium-ion batteries are disassembled, separated, soaked in solvents for cleaning, and dried to obtain crude negative electrode graphite; the negative electrode graphite is extracted and washed with a low eutectic solvent, and the graphite extracted with the low eutectic solvent is obtained after magnetic stirring, ultrasonic vibration, filtration, and drying; finally, graphene is prepared by oxidation and reduction by the Hummers method, wherein the oxidant is concentrated sulfuric acid, potassium persulfate and phosphorus pentoxide, and the reducing agent is hydrogen peroxide. In this method, the residual metal content in the negative electrode carbon material after extraction and washing with a low eutectic solvent is low, and the graphite recovery rate is high, but the required reagents are many and the cost of the low eutectic solvent is high, which is not suitable for large-scale production; and the phosphorus pentoxide in the oxidant component is highly corrosive and toxic, which can easily cause great damage to the human body.
[0005] CN107879332A discloses a method for preparing graphene by exfoliating graphite using a spatiotemporal synchronous ultrasonic ball milling method, wherein graphite and an exfoliating agent are placed in an ultrasonic ball milling device, wherein the exfoliating agent may be any one of N-methylpyrrolidone, isopropanol, acetone, chloroform, fluorinated aromatics, octafluorotoluene, pentafluorobenzocyanate, pentafluoropyrimidine, chloroform, cyclopentanone, dimethyl sulfoxide, tetrahydrofuran, γ-butyrolactone, or 1,3-dimethyl-2-imidazolidinone, and graphene is prepared by exfoliation using ultrasound and ball milling. The disadvantages of the above method are that the ball milling speed is high, the energy consumption is large, and the ball and graphite loss are large, which is not conducive to large-scale application. CN11438996 A discloses a method for preparing graphene by intercalating graphite with explosives, wherein a binary graphite intercalation compound is placed in a nitromethane solvent, and a sufficient amount of carbon dioxide is injected as a protective medium, and the explosive is ignited, and a large amount of gas is generated during the explosion to exfoliate the graphite. The process has poor safety, and the short duration of the explosion impact will lead to problems such as insufficient graphite exfoliation. In addition, CN110127679A discloses a ball milling method for preparing graphene from nitromethane intercalated graphite, in which a binary graphite intercalation compound and dry ice are placed in a sealed ball mill. During the ball milling process, nitromethane explodes and decomposes heat, gas, and ball milling to exfoliate the graphite. This process combines explosion with ball milling to ensure sufficient graphite exfoliation. The above methods have simple processes, but all have safety hazards of large explosion impact force and are not suitable for large-scale production applications.
[0006] Compared with multilayer graphene, single-layer graphene has obvious advantages in application performance, such as high electron mobility, thermal conductivity, light transmittance, mechanical properties, heat conduction and energy conversion efficiency. Graphene prepared by existing technology is often multilayer graphene, and it is difficult to prepare single-layer or few-layer graphene with less than 2 layers.
[0007] In summary, the existing graphite preparation technology for graphene has the problems of high cost, long time consumption, poor safety, low degree of graphite exfoliation, and difficulty in obtaining single-layer or few-layer graphene. Therefore, it is worthy of attention and research to develop a green process and technology for preparing single-layer or few-layer graphene with low reagent consumption, simple process and high safety. Summary of the invention
[0008] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing single-layer or few-layer graphene using expanded graphite as raw material. The present invention uses expanded graphite as raw material, simplifies the oxidation reaction process of waste graphite, and then directly prepares nearly single-layer graphene by ultrasonic dispersion of oxidized graphite and high-temperature spray pyrolysis. The process flow is simple and no additional reducing agent needs to be added. The expanded graphite here can be expanded graphite or recycled graphite separated from the negative electrode material of lithium-ion batteries. This technology can not only alleviate the pressure of waste lithium-ion batteries on the ecological environment and save graphite resources, but also can prepare single-layer or few-layer graphene, which has significant economic benefits and has far-reaching significance for the sustainable development of the lithium-ion battery industry.
[0009] To achieve the above object, the present invention provides a method for preparing single-layer or few-layer graphene using expanded graphite as raw material, comprising the following steps:
[0010] (1) oxidizing expanded graphite with an oxidant to form oxidized graphite; the expanded graphite is expanded graphite and / or recycled graphite separated from negative electrode materials of lithium-ion batteries; the oxidant comprises concentrated sulfuric acid and potassium permanganate; the oxidation is specifically: mixing the expanded graphite with a mixed oxidant of concentrated sulfuric acid and potassium permanganate, first reacting at an ice-water bath temperature, and then heating the mixture to a medium temperature of less than or equal to 70° C. to cause an oxidation reaction to obtain oxidized graphite;
[0011] (2) The graphite oxide is ultrasonically dispersed in a solvent and then subjected to high-temperature spray pyrolysis to prepare a single-layer or few-layer graphene.
[0012] Preferably, the acquisition of the recycled graphite comprises the following steps: soaking the disassembled and separated lithium-ion battery negative electrode material in an organic solvent to obtain waste graphite; acid-washing the waste graphite to remove impurities and drying to obtain the recycled graphite after impurities removal, that is, the recycled graphite separated from the lithium-ion battery negative electrode material.
[0013] Preferably, the lithium-ion battery is a lithium-ion battery whose positive electrode material is one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate.
[0014] Preferably, the organic solvent is one or more of methanol, ethanol, isopropanol, acetone, N-methylformamide, N-methylpyrrolidone, dimethylacetamide, dimethylformamide, triethyl phosphate, ionic liquids (such as 1-butyl-3-methylimidazolium hexafluorophosphate, 1-butyl-2,3-dimethylpyridinium salt, tetraethylammonium salt, trioctyltetradecylphosphatidyl salt, glycine onium salt, 1-butyl-3-methylamidine salt, etc.).
[0015] Preferably, the solid-liquid ratio of the disassembled and separated lithium-ion battery negative electrode material to the organic solvent is 1:10-1:100 g / mL, the immersion temperature is 20-60° C., and the time is 5-60 min.
[0016] Preferably, the impurity removal agent used in the pickling and impurity removal is Lewis acid, and more preferably one or more of citric acid, formic acid, hydrochloric acid, hydrofluoric acid, and trifluoromethanesulfonic acid.
[0017] Preferably, the concentration of the Lewis acid is 0.05-3 mol / L; the solid-liquid ratio of the waste graphite to the Lewis acid is 1:10-1:200 g / mL, the reaction time is 10-90 min, and the temperature is 30-90°C.
[0018] Preferably, the oxidation in step (1) is as follows: the expanded graphite is mixed with a mixed oxidant of concentrated sulfuric acid and potassium permanganate and reacted at an ice-water bath temperature for 60-180 minutes, and then heated to a medium temperature of 30-70° C. and reacted for 4-10 hours.
[0019] Further preferably, the oxidation in step (1) is as follows: the expanded graphite is mixed with a mixed oxidant of concentrated sulfuric acid and potassium permanganate and reacted at an ice-water bath temperature for 60-90 minutes, and then heated to a medium temperature of 40-60° C. and reacted for 7-9 hours.
[0020] Preferably, the usage ratio of the expanded graphite, concentrated sulfuric acid and potassium permanganate is 1 g: (15-25) mL: (1-5) g.
[0021] Preferably, the power of the ultrasonic dispersion is 150W-270W; the time of the ultrasonic dispersion is 10-60min.
[0022] Preferably, the solvent is one or more of water, isopropanol, N-methylformamide, methanol and ethanol.
[0023] Preferably, the high temperature spray pyrolysis has a pyrolysis temperature of 100-500°C, more preferably 150-300°C.
[0024] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0025] (1) The present invention has experimentally found that the recycled graphite separated from the negative electrode material of lithium-ion batteries may have a similar structure to expanded graphite. In the present invention, the two are collectively referred to as expanded graphite. The expanded graphite is combined with the simplified oxidation process proposed by the present invention to obtain oxidized graphite, and then single-layer or few-layer graphene can be prepared by high-temperature spray pyrolysis after ultrasound. In the process of chemical oxidation of expanded graphite, the distance between graphite layers increases due to the access of oxygen-containing functional groups. Then, the high-temperature spray pyrolysis technology that combines exfoliation and reduction is used to exfoliate and reduce the oxidized graphite to graphene, thereby realizing the regeneration of waste graphite into high-value-added near-single-layer graphene products. The technical process is simple, reduces the use of chemical reagents, has low cost, and is controllable in quality, and is suitable for large-scale industrial production.
[0026] (2) The present invention separates and recovers high-purity graphite from waste lithium-ion batteries, using a mixed oxidant of concentrated sulfuric acid and potassium permanganate. During the oxidation process, graphite oxide with a high degree of oxidation can be prepared only through low-temperature and medium-temperature reactions, and the process is short in time. The graphite oxide is then ultrasonically dispersed and then sprayed and pyrolyzed at high temperature to obtain single-layer or few-layer graphene. In the experiment, the graphite recovered from waste batteries of the present invention was replaced with flake graphite or expanded graphite. When the oxidation-ultrasound-high-temperature spray pyrolysis process of the present invention was used, it was found that only 34 layers of graphene could be obtained by using flake graphite, but nearly single-layer graphene could be obtained by using expanded graphite, just like the recovered graphite separated from lithium-ion batteries of the present invention. However, when the oxidation process is replaced by the low-temperature-medium-temperature two-step oxidation process in the embodiment of the present invention with a low-temperature-medium-temperature-high-temperature three-step oxidation process similar to the traditional Hummers oxidation method, the flake graphite, the commercially available expanded graphite, and the recycled graphite in the embodiment of the present invention cannot obtain nearly single-layer graphene, which shows that the improved oxidation process of the present invention is crucial for the expanded graphite to obtain nearly single-layer graphene, and the graphite material recovered from the waste lithium-ion battery may be similar to the expanded graphite structure due to the influence of battery charging and discharging, and is more suitable for the oxidation-ultrasound-high-temperature spray pyrolysis process of the present invention to obtain single-layer or few-layer graphene than ordinary flake graphite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic flow chart of a method for separating graphite from negative electrode materials of waste lithium-ion batteries and preparing graphene provided by the present invention;
[0028] Figure 2 The thermogravimetric curve of graphite oxide prepared in Example 1 under air conditions;
[0029] Figure 3 Schematic diagram of the microstructure change of graphite during the preparation process of the present invention;
[0030] Figure 4FTIR spectrum of graphite oxide prepared in Example 1;
[0031] Figure 5 The XRD patterns of the graphene prepared in Example 1 are compared with those of commercial graphene;
[0032] Figure 6 SEM comparison images of graphene prepared in Example 1 and commercial graphene;
[0033] Figure 7 The Raman spectrum of the graphene prepared in Example 1;
[0034] Figure 8 The Raman spectrum of the graphene prepared in Example 3;
[0035] Fig. 9 The Raman spectrum of the graphene prepared in Example 4;
[0036] Fig.10 XRD pattern of graphite oxide prepared in Comparative Example 1;
[0037] Fig.11 The SEM images of graphene prepared in Comparative Examples 1 to 3;
[0038] Fig.12 The Raman spectrum of graphene prepared in Comparative Example 4;
[0039] Fig.13 The Raman spectrum of graphene prepared in Comparative Example 5;
[0040] Fig.14 FTIR spectrum of graphite oxide prepared in Comparative Example 6;
[0041] Fig.15 The Raman spectrum of graphene prepared in Comparative Example 6;
[0042] Fig.16 FTIR spectrum of graphite oxide prepared in Comparative Example 7;
[0043] Fig.17 The Raman spectrum of graphene prepared in Comparative Example 7;
[0044] Fig.18 The Raman spectrum of graphene prepared in Comparative Example 8;
[0045] Fig.19 The Raman spectrum of graphene prepared in Comparative Example 9;
[0046] Fig. 20 This is the Raman spectrum of graphene prepared in Comparative Example 10. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0048] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0049] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0050] The present invention provides a method for preparing single-layer or few-layer graphene using expanded graphite as a raw material, comprising the following steps:
[0051] (1) oxidizing the expanded graphite with an oxidant to form oxidized graphite; in the present invention, the expanded graphite and the recovered graphite separated from the negative electrode material of the lithium ion battery are collectively referred to as expanded graphite; the oxidant used in the oxidation process of the present invention comprises concentrated sulfuric acid and potassium permanganate; the oxidation process is specifically as follows: the expanded graphite is mixed with a mixed oxidant of concentrated sulfuric acid and potassium permanganate, and then reacted at an ice water bath temperature, and then heated to a medium temperature of less than or equal to 70° C. to cause an oxidation reaction to obtain oxidized graphite;
[0052] (2) The graphite oxide is ultrasonically dispersed in a solvent and then subjected to high-temperature spray pyrolysis to prepare a single-layer or few-layer graphene.
[0053] The single-layer or few-layer graphene described in the present invention refers to graphene with a layer number less than or equal to 2, preferably less than 1.5 layers.
[0054] In a preferred embodiment, the oxidation is as follows: the expanded graphite (i.e., expanded graphite and / or recovered graphite) is mixed with a mixed oxidant of concentrated sulfuric acid and potassium permanganate and reacted at an ice-water bath temperature for 60-180 minutes, and then heated to a medium temperature of 30-70° C. and reacted for 4-10 hours.
[0055] When using the traditional Hummers method to oxidize graphite to prepare graphite oxide, high-purity graphite is generally first mixed with concentrated sulfuric acid, and then undergoes a low-temperature (ice-water bath)-medium temperature (32℃-38℃)-high temperature (>90℃) oxidation reaction process, and potassium permanganate is added during the ice-water bath reaction to prepare graphite oxide. Concentrated sulfuric acid, as an intercalating agent, first enters the edge of the graphite layer or the defects of the graphite structure and oxidizes it. Polar sulfuric acid molecules and hydrogen sulfate ions gradually insert into the graphite structure layer domain through intermolecular forces and electrostatic attraction to form sulfuric acid-graphite intercalation compounds. The reaction equation is: H 2 SO 4 +G+[O]→H 2 O+[G+HSO 4 - ·H 2 SO 4 ]. Then potassium permanganate is added, and its ionized oxygen-containing functional groups enter the interlayer along the edge of the graphite layer, further oxidizing the sulfuric acid-graphite interlayer compound. The reaction equation is: MnO 4 - +[G+HSO 4 - ·H 2 SO 4 ]→MnO 2 +SO x +H 2 O+GO, the oxidation process increases the interlayer spacing of the graphite structure, and its hybridization mode changes from sp 2 Transformed into sp 3 .
[0056] In the present invention, when preparing oxidized graphite by oxidizing expanded graphite, i.e., expanded graphite or high-purity graphite separated and recovered from negative electrode materials of waste lithium-ion batteries, concentrated sulfuric acid and potassium permanganate as oxidants are mixed with the expanded graphite at the same time, and oxidation reactions are carried out at low temperature (ice water bath) and medium temperature (30-70°C) to prepare high-purity graphite. Different from the traditional Hummers method, the present invention simultaneously mixes concentrated sulfuric acid and potassium permanganate with high-purity graphite for reaction, and obvious intercalation and oxidation reactions occur under the action of the mixed oxidant system, and heat is released, the graphite lattice expands and / or peels off, and a large number of oxygen-containing functional groups are gradually connected. As the reaction time in the medium temperature stage is prolonged, the graphite phase gradually decreases until it disappears. The reaction equation is: H 2 SO 4 +MnO 4 - +G→GO+MnSO 4 +O 2 +H 2 O. The graphite oxidation mechanism of the present invention is significantly different from the Hummers method, and graphite oxide GO can be directly synthesized in one step to improve the reaction efficiency.
[0057] The existing Hummers method or improved Hummers method uses concentrated sulfuric acid and potassium permanganate as oxidants to prepare graphite oxide. Concentrated sulfuric acid and potassium permanganate are introduced sequentially rather than simultaneously. Concentrated sulfuric acid and graphite are first mixed at low temperature to undergo an oxidation reaction. Potassium permanganate is added during the low temperature reaction to continue the oxidation reaction, and then the temperature is raised to a medium temperature, and finally the temperature is raised to a high temperature to continue the oxidation reaction, thereby preparing graphite oxide. However, the present invention directly mixes two oxidants with battery recycled graphite or expanded graphite at the same time, and omits the high temperature reaction step. Experiments have found that the graphite oxide prepared in this way can be used to prepare a few-layer or single-layer graphene according to the ultrasonic-high temperature spray pyrolysis method of the present invention, and can also avoid the technical defect of manganese dioxide impurities being doped in the graphene product when concentrated sulfuric acid and potassium permanganate are introduced step by step. The possible reason is that the present invention uses recycled graphite obtained by separating and removing impurities from lithium ion battery negative electrode materials as a raw material for oxidation exfoliation and reduction to prepare graphene. It is speculated that the lithium ion battery charging and discharging process has a certain amplification effect on the graphite interlayer spacing, making it possible to prepare single-layer or few-layer graphene according to the method of the present invention, just like expanded graphite, compared with ordinary graphite such as flake graphite.
[0058] In step (1), since a large amount of heat is released during the oxidation reaction, the oxidation reaction is first reacted in an ice-water bath (0° C.) for 60-180 min and then reacted at a medium temperature of 30-70° C. for 4-10 h. It is further preferred that the ice-water bath reaction time is 60-90 min, the medium temperature reaction temperature is 40-60° C., and the medium temperature reaction time is 7-9 h.
[0059] In some embodiments, the usage ratio of the expanded graphite, concentrated sulfuric acid and potassium permanganate is 1 g:(15-25) mL:(1-5) g, and more preferably 1 g:(20-25) mL:(2-4) g.
[0060] In some embodiments, hydrogen peroxide is added to the system after the oxidation reaction is completed to consume the potassium permanganate that has not reacted during the reaction.
[0061] In some embodiments, the power of the ultrasonic dispersion in step (2) is 150W-270W, preferably 200W-250W; the time of ultrasonic dispersion is 10-60min, preferably 20-40min. The present invention ultrasonically disperses graphite oxide in a solvent to facilitate the next step of spray pyrolysis. During the ultrasonic dispersion of graphite oxide, exfoliation occurs to form graphene oxide.
[0062] In some embodiments, the solvent in step (2) is one or more of water, isopropanol, N-methylformamide, methanol and ethanol.
[0063] In some embodiments, the high temperature spray pyrolysis in step (2) has a pyrolysis temperature of 100-500°C, preferably 150-300°C.
[0064] In some embodiments, a general-purpose spray pyrolysis dryer or similar equipment is used, and the spray pyrolysis temperature is represented by the air inlet temperature, which is set to 100-500°C, preferably 150-300°C, and the liquid spray rate is 10-200ml / h, preferably 30-100ml / h, and further preferably 40-60ml / h. The liquid spray rate determines the residence time of the material in the spray pyrolysis equipment.
[0065] In some embodiments, the obtaining of the recycled graphite includes the following steps: soaking and separating the disassembled and separated lithium-ion battery negative electrode material in an organic solvent to obtain waste graphite; and acid-washing and removing impurities from the waste graphite and drying to obtain the recycled graphite after impurities are removed.
[0066] Figure 1 The present invention provides a schematic flow chart of a method for separating graphite from anode materials of waste lithium-ion batteries and preparing single-layer or few-layer graphene in some embodiments of the present invention. Specifically, the method comprises the following steps:
[0067] (1) Cutting up the waste lithium-ion battery negative electrode material and mixing it with an organic solvent according to a certain solid-liquid ratio, stirring the mixed system with a magnetic force, and filtering and separating after a certain reaction time to obtain waste graphite;
[0068] (2) the waste graphite obtained in step (1) is vacuum dried and then acid leached to remove metal impurities therein, thereby obtaining recycled graphite after impurity removal;
[0069] (3) chemically oxidizing the recovered graphite in step (2) using an oxidant to prepare graphite oxide;
[0070] (4) preparing graphene by high-temperature spray pyrolysis after ultrasonically dispersing the graphite oxide described in step (3) into a liquid phase; wherein ultrasound and high-temperature spray pyrolysis are used in combination, and the graphite oxide is firstly ultrasonically dispersed uniformly into a liquid phase solvent, and under this action, the graphite oxide is exfoliated into graphene oxide, and then introduced into a high-temperature spray pyrolysis device, where the organic solvent containing the graphite oxide is atomized to form tiny droplets due to the acceleration effect, and then the droplets are carried in an air flow and sent into a heating reaction furnace, where the organic solvent in the droplets evaporates under the action of high temperature, and the oxygen-containing functional groups in the graphene oxide undergo a deoxygenation reaction to be reduced to graphene.
[0071] The present invention provides a method for separating graphite from waste lithium-ion battery negative electrode materials and preparing graphene. The method first uses organic solvent immersion to separate waste graphite and copper foil current collector, then uses Lewis acid to purify and remove impurities, then oxidizes it to graphite oxide, and after ultrasonic dispersion, it is exfoliated and reduced to a few layers or single layers of graphene by high-temperature spray pyrolysis. The method is simple in process, short in preparation cycle, low in reagent consumption, low in cost, and can be mass-produced, solving the problems of high cost, high energy consumption, poor safety, and low degree of graphite exfoliation in existing graphene preparation. In addition, the regenerated graphene can be applied to fields such as energy storage, catalysis, and environmental pollution control, and can effectively improve the value of graphite regeneration and recycling.
[0072] The waste lithium-ion batteries described in the present invention can be various lithium-ion batteries containing graphite negative electrodes, including but not limited to lithium-ion batteries whose positive electrode materials are one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, etc.
[0073] The binders used for negative electrodes of lithium-ion batteries mainly include polyvinylidene fluoride, sodium carboxymethyl cellulose, polyacrylic acid, styrene-butadiene rubber, polyvinyl alcohol, polyimide, etc. When soaked in organic solvents, the solvent molecules penetrate between the polymer chains, weakening the van der Waals forces and hydrogen bonds between the polymer molecules. When the interaction force between the solvent molecules and the polymer chains is greater than the interaction force between the polymer molecules, the polymer chains are disassembled, thereby achieving the dissolution of the binder and efficiently separating the waste graphite. In step (1), various organic solvents capable of separating waste graphite can be selected according to the binder material used in the negative electrode of the waste lithium-ion battery, including but not limited to one or more polar solvents such as methanol, ethanol, isopropanol, acetone, N-methylformamide, N-methylpyrrolidone, dimethylacetamide, dimethylformamide, triethyl phosphate, ionic liquids (such as 1-butyl-3-methylimidazolium hexafluorophosphate, 1-butyl-2,3-dimethylpyridinium salt, tetraethylammonium salt, trioctyltetradecylphosphatide salt, glycine salt, 1-butyl-3-methylamidine salt, etc.).
[0074] In some embodiments, the solid-liquid ratio of the disassembled and separated lithium-ion battery negative electrode material to the organic solvent is 1:10-1:100 g / mL, the immersion temperature is 20-60°C, and the time is 5-60 min. The further preferred solid-liquid ratio is 1:10-1:50 g / L, the immersion temperature is 30-60°C, and the time is 20-40 min.
[0075] In some embodiments, the impurity removal agent used for the pickling and impurity removal in step (2) is a Lewis acid, including but not limited to one or more of citric acid, formic acid, hydrochloric acid, hydrofluoric acid, trifluoromethanesulfonic acid, etc.; the Lewis acid concentration is 0.05-3 mol / L, the solid-liquid ratio of the waste graphite to the Lewis acid is 1:10-1:200 g / mL, the reaction time is 10-90 min, and the temperature is 30-90°C. It is further preferred that the Lewis acid concentration is 0.05-2 mol / L, the solid-liquid ratio is 1:10-1:50 g / mL, the reaction time is 20-40 min, and the temperature is 50-90°C.
[0076] In some embodiments, the recovery rate of waste graphite in step (1) reaches more than 95%, and the metal impurity removal rate of waste graphite in the acid washing and impurity removal process in step (2) reaches more than 99%.
[0077] The present invention uses expanded graphite or graphite recovered from the negative electrode of waste lithium-ion batteries as raw materials, obtains oxidized graphite through a simplified oxidation process, and then prepares single-layer or few-layer graphene in combination with ultrasonic dispersion and high-temperature spray pyrolysis process. The present invention adopts chemical oxidation combined with high-temperature spray pyrolysis process to prepare graphene. Compared with the Hummers method and the improved Hummers process, the process is simpler and does not require the addition of additional reducing agents. This technology can not only alleviate the pressure of waste lithium-ion batteries on the ecological environment and save graphite resources, but also has significant economic benefits, which has far-reaching significance for the sustainable development of the lithium-ion battery industry.
[0078] The flake graphite and expanded graphite used in the embodiments of the present invention are both commercially available products.
[0079] The following are specific embodiments:
[0080] Example 1
[0081] This embodiment provides a method for separating graphite from the negative electrode sheet of waste lithium-ion batteries by high-temperature spray pyrolysis and preparing graphene. Figure 1 A flow chart of a method for separating graphite from a negative electrode sheet of a waste lithium-ion battery and preparing graphene by high-temperature spray pyrolysis is provided in this embodiment, comprising the following steps:
[0082] (1) Cut the negative electrode of the waste lithium-ion battery into 1 cm 2 The size was mixed with triethyl phosphate at a solid-liquid ratio of 1:10 g / mL. The mixed system was stirred magnetically and reacted at 20° C. for 60 minutes. Then, the recovered graphite was separated by filtration. The recovery rate of the graphite reached 95%.
[0083] (2) The recovered graphite obtained in step (1) is vacuum dried and then leached with citric acid to remove metal impurities therein to obtain high-purity graphite, the citric acid concentration is 0.05 mol / L, the solid-liquid ratio is 1:50 g / mL, 90° C., 40 min, and the metal impurity removal rate reaches 99.5%.
[0084] (3) The high-purity graphite described in step (2) is chemically oxidized to form graphite oxide using an oxidant consisting of concentrated sulfuric acid and potassium permanganate, high-purity graphite: concentrated sulfuric acid: potassium permanganate = 1g: 25mL: 3g. The oxidation reaction is first reacted in an ice-water bath for 90 minutes, and then reacted at a medium temperature of 50°C for 8 hours to obtain a golden yellow graphite oxide solution, and then hydrogen peroxide is added until no bubbles are generated, and then filtered after standing, and finally washed with deionized water until neutral, and then dried to obtain a graphite oxide powder with a good degree of oxidation, and its FTIR infrared spectrum is as follows: Figure 4 As shown, it indicates that there are oxygen-containing groups such as carbonyl, hydroxyl, and epoxy groups in graphite oxide.
[0085] (4) The graphite oxide described in step (3) was dispersed in water at 240W ultrasonic for 30 minutes, and then graphene was prepared by high temperature spray pyrolysis at 300°C, with an air inlet temperature of 300°C, a liquid spray rate of 50ml / h, and an air atmosphere. Its XRD spectrum, SEM image and Raman spectrum are as follows: Figure 5 , Figure 6 and Figure 7 As shown in the XRD spectrum, it can be seen that the diffraction peak appears at a 2θ angle of 26°, corresponding to the (0 0 2) crystal plane of graphene. This is due to the sp 2 The hexagonal lattice structure of hybridized carbon atoms. SEM images show that graphene has a smooth surface, a lighter color and obvious wrinkles. Raman test results show that the G peak appears at 1585.5cm -1 At, according to the formula W G =1581.6+11 / (1+n 1.6 ) calculated that the number of graphene layers n is 1.45, indicating that the number of graphene layers prepared by this method is relatively small.
[0086] Figure 2 The thermogravimetric curve of the graphite oxide prepared in Example 1 under air conditions; it can be seen that the weight loss of the sample is mainly divided into four stages, the first stage 28-125°C due to the loss of adsorbed water, the weight loss is 15.22%; the second stage 125-189°C due to the loss of water molecules directly connected to the oxygen-containing functional groups by hydrogen bonds, the weight loss rate is 10.71%; the third stage 189-387°C due to the thermal decomposition of the oxygen-containing functional groups in the sample, the weight loss rate is 16.84%; finally, the exothermic peak begins to appear at 515.2°C, which is due to the combustion of the carbon skeleton. Therefore, the temperature of high-temperature spray pyrolysis reduction of graphite oxide should be lower than 500°C.
[0087] Figure 3 Schematic diagram of the microstructure change of graphite during the preparation process of an embodiment of the present invention; first, the collected lithium ion battery negative electrode graphite is separated and purified to obtain recycled graphite, also known as expanded graphite, which is chemically oxidized to obtain oxidized graphite, and then ultrasonically dispersed and high-temperature spray pyrolysis are used to prepare graphene.
[0088] Figure 4 This is the FTIR spectrum of graphite oxide prepared in Example 1. It can be seen that the graphite oxide prepared under this condition contains oxygen-containing groups such as carbonyl, carboxyl, and epoxy, indicating that its degree of oxidation is high.
[0089] Figure 5 The XRD spectrum of graphene prepared in Example 1 shows that the diffraction peak appears at a 2θ angle of 26°, corresponding to the (0 0 2) crystal plane of graphene. This is due to the sp 2 It is caused by the hexagonal lattice structure of hybridized carbon atoms.
[0090] Figure 6 The SEM comparison images of the graphene prepared in Example 1 and commercial graphene show that the prepared graphene has a relatively smooth surface, and has a lighter color and obvious wrinkles than the commercial graphene, indicating that it has fewer layers.
[0091] Figure 7 This is the Raman spectrum of graphene prepared in Example 1; it can be seen that the G peak appears at 1585.5 cm -1 The D peak appears at 1347.1 cm -1 The number of layers is calculated to be 1.45. The conductivity of the graphene prepared in this embodiment is measured to be 1.66×10 7 S / m.
[0092] Example 2
[0093] (1) Cut the negative electrode of the waste lithium-ion battery into 1 cm 2 The size was mixed with N-methylpyrrolidone at a solid-liquid ratio of 1:100 g / mL. The mixed system was stirred magnetically and reacted at 60° C. for 20 minutes, then filtered and separated to obtain recovered graphite. The recovery rate of graphite reached 99%.
[0094] (2) The recovered graphite obtained in step (1) is vacuum dried and then leached with hydrochloric acid to remove metal impurities therein to obtain high-purity graphite. The hydrochloric acid concentration is 2 mol / L, the solid-liquid ratio is 1:10 g / mL, 50° C., and 20 min. The metal impurity removal rate reaches 99.6%.
[0095] (3) The high-purity graphite described in step (2) is chemically oxidized using an oxidant consisting of concentrated sulfuric acid and potassium permanganate to form graphite oxide, waste graphite: concentrated sulfuric acid: potassium permanganate = 1g: 15mL: 4g. The oxidation reaction is first reacted in an ice-water bath for 90min, and then reacted at a medium temperature of 60°C for 8h to obtain a golden yellow graphite oxide solution, and then hydrogen peroxide is added until no bubbles are generated, and the solution is filtered after standing, and finally washed with deionized water until neutral, and then dried to obtain graphite oxide.
[0096] (4) The graphite oxide described in step (3) was dispersed in ethanol at 240W ultrasonic for 60min and then sprayed and pyrolyzed at 250°C to prepare graphene. The air inlet temperature was set at 250°C, the liquid spray rate was 50ml / h, and the atmosphere was air.
[0097] Example 3
[0098] (1) Cut the negative electrode of the waste lithium-ion battery into 1 cm 2 The size was mixed with N-methylformamide at a solid-liquid ratio of 1:50 g / mL, the mixed system was stirred magnetically, reacted at 40°C for 40 minutes, and then filtered and separated to obtain recovered graphite, with a recovery rate of graphite reaching 99%;
[0099] (2) The recovered graphite obtained in step (1) is vacuum dried and then leached with sulfuric acid to remove metal impurities therein to obtain high-purity graphite, the sulfuric acid concentration is 0.5 mol / L, the solid-liquid ratio is 1:100 g / mL, 70° C., 30 min, and the metal impurity removal rate reaches 99.5%.
[0100] (3) The high-purity graphite described in step (2) is chemically oxidized using an oxidant consisting of concentrated sulfuric acid and potassium permanganate to form graphite oxide, waste graphite: concentrated sulfuric acid: potassium permanganate = 1g: 20mL: 2g. The oxidation reaction is first reacted in an ice-water bath for 90min, and then reacted at a medium temperature of 50°C for 10h to obtain a golden yellow graphite oxide solution, and then hydrogen peroxide is added until no bubbles are generated, and then filtered after standing, and finally washed with deionized water until neutral, and then dried to obtain graphite oxide.
[0101] (4) The graphite oxide described in step (3) was dispersed by ultrasonic method at 240W for 30min in N-methylformamide and then sprayed and pyrolyzed at 200℃ to prepare graphene oxide. The air inlet temperature was set at 200℃, the liquid spray rate was 50ml / h, and the air atmosphere was air. The Raman spectrum of graphene prepared in Example 3 is shown in Figure 8 As shown, it can be seen that the G peak appears at 1585.4 cm -1 The D peak appears at 1353.8 cm -1 After calculation, the number of layers is 1.49.
[0102] Example 4
[0103] (1) Expanded graphite is chemically oxidized to form graphite oxide using an oxidant consisting of concentrated sulfuric acid and potassium permanganate, expanded graphite: concentrated sulfuric acid: potassium permanganate = 1 g: 25 mL: 3 g. The oxidation reaction is first carried out in an ice-water bath for 90 min, and then at a medium temperature of 50° C. for 8 h to obtain a golden yellow graphite oxide solution, and then hydrogen peroxide is added until no bubbles are generated, and the solution is filtered after standing, and finally washed with deionized water until neutral, and then dried to obtain graphite oxide powder with a good degree of oxidation.
[0104] (2) The graphite oxide described in step (1) was dispersed in water at 240W ultrasonic for 30 minutes, and then graphene was prepared by high-temperature spray pyrolysis at 300°C, with an air inlet temperature of 300°C, a liquid spray rate of 50ml / h, and an air atmosphere. Raman test results Fig. 9 The G peak appears at 1585.8 cm -1 At, according to the formula W G =1581.6+11 / (1+n 1.6 ) calculated that the number of graphene layers n is 1.35, indicating that the number of graphene layers prepared by this method is relatively small.
[0105] Comparative Example 1
[0106] (1) Cut the negative electrode of the waste lithium-ion battery into 1 cm 2 The size was mixed with triethyl phosphate at a solid-liquid ratio of 1:10 g / mL. The mixed system was stirred magnetically and reacted at 20° C. for 60 minutes. Then, the recovered graphite was separated by filtration. The recovery rate of the graphite reached 95%.
[0107] (2) The recovered graphite obtained in step (1) is vacuum dried and then leached with citric acid to remove metal impurities therein to obtain high-purity graphite, the citric acid concentration is 0.05 mol / L, the solid-liquid ratio is 1:50 g / mL, 90° C., 40 min, and the metal impurity removal rate reaches 99.5%.
[0108] (3) The high-purity graphite described in step (2) is chemically oxidized to form graphite oxide using an oxidant consisting of concentrated sulfuric acid and potassium permanganate, high-purity graphite: concentrated sulfuric acid: potassium permanganate = 1g: 10mL: 0.5g, the oxidation reaction is first reacted in an ice-water bath for 90min, and then reacted at a medium temperature of 50°C for 8h to obtain a graphite oxide solution, and then hydrogen peroxide is added until no bubbles are generated, and the solution is filtered after standing, and finally washed with deionized water until neutral, and then dried to obtain graphite oxide powder. Due to the insufficient dosage of the oxidant concentrated sulfuric acid and potassium permanganate, the degree of oxidation is low, and the characteristic peaks of graphite are still retained, and the characteristic peaks of graphite oxide are not observed. Its XRD spectrum is as follows: Fig.10 shown.
[0109] (4) The graphite oxide described in step (3) was dispersed in water at 240W ultrasonic for 30 minutes, and then graphene was prepared by high-temperature spray pyrolysis at 300°C. The air inlet temperature was set at 300°C, the liquid spray rate was 50ml / h, and the air atmosphere was air. The SEM image of the product prepared by this process is as follows: Fig.11 As shown in Comparative Example 1, the layered structure of graphite is still maintained.
[0110] Comparative Example 2
[0111] (1) Cut the negative electrode of the waste lithium-ion battery into 1 cm 2 The size was mixed with N-methylpyrrolidone at a solid-liquid ratio of 1:100 g / mL. The mixed system was stirred magnetically and reacted at 60° C. for 20 minutes, then filtered and separated to obtain recovered graphite. The recovery rate of graphite reached 99%.
[0112] (2) The recovered graphite obtained in step (1) is vacuum dried and then leached with hydrochloric acid to remove metal impurities therein to obtain high-purity graphite. The hydrochloric acid concentration is 2 mol / L, the solid-liquid ratio is 1:10 g / mL, 50° C., and 20 min. The metal impurity removal rate reaches 99.6%.
[0113] (3) The high-purity graphite described in step (2) is chemically oxidized using an oxidant consisting of concentrated sulfuric acid and potassium permanganate to form oxidized graphite, waste graphite: concentrated sulfuric acid: potassium permanganate = 1g: 15mL: 4g. The oxidation reaction is first reacted in an ice-water bath for 90min, and then reacted at a medium temperature of 60°C for 8h to obtain an oxidized graphite solution, and then hydrogen peroxide is added until no bubbles are generated, and the solution is allowed to stand and then filtered, and finally washed with deionized water until neutral, and then dried to obtain oxidized graphite.
[0114] (4) The graphite oxide described in step (3) was dispersed in ethanol at 240W ultrasonic for 60 minutes and then dried to prepare graphene. The SEM image of the product obtained by ultrasonication without reduction is as follows: Fig.11 As shown in Comparative Example 2, it still maintains a layered structure.
[0115] By comparing the graphene prepared in Comparative Example 2 with that prepared in Example 1, it was found that only ultrasound without spray pyrolysis failed to achieve complete exfoliation and reduction of graphite oxide.
[0116] Comparative Example 3
[0117] (1) Cut the negative electrode of the waste lithium-ion battery into 1 cm 2 The size was mixed with N-methylpyrrolidone at a solid-liquid ratio of 1:100 g / mL. The mixed system was stirred magnetically and reacted at 60° C. for 20 minutes, then filtered and separated to obtain recovered graphite. The recovery rate of graphite reached 99%.
[0118] (2) The recovered graphite obtained in step (1) is vacuum dried and then leached with hydrochloric acid to remove metal impurities therein to obtain high-purity graphite. The hydrochloric acid concentration is 2 mol / L, the solid-liquid ratio is 1:10 g / mL, 50° C., and 20 min. The metal impurity removal rate reaches 99.6%.
[0119] (3) The high-purity graphite described in step (2) is chemically oxidized using an oxidant consisting of concentrated sulfuric acid and potassium permanganate to form oxidized graphite, waste graphite: concentrated sulfuric acid: potassium permanganate = 1g: 15mL: 4g. The oxidation reaction is first reacted in an ice-water bath for 90min, and then reacted at a medium temperature of 60°C for 8h to obtain an oxidized graphite solution, and then hydrogen peroxide is added until no bubbles are generated, and the solution is allowed to stand and then filtered, and finally washed with deionized water until neutral, and then dried to obtain oxidized graphite.
[0120] (4) After the graphite oxide described in step (3) is dispersed in an ethanol solution, graphene oxide is directly prepared using a 90°C high-temperature spray pyrolysis device. The air inlet temperature is set at 90°C, the liquid spray rate is 50ml / h, and the air atmosphere is air. The SEM image of the product obtained by this process is as follows Fig.11 As shown in Comparative Example 3, under the action of ultrasound and low temperature, the reduction reaction is incomplete and the structure is still layered.
[0121] Comparative Example 4
[0122] (1) Cut the negative electrode of the waste lithium-ion battery into 1 cm 2 The size was mixed with triethyl phosphate at a solid-liquid ratio of 1:10 g / mL. The mixed system was stirred magnetically and reacted at 20° C. for 60 minutes. Then, the recovered graphite was separated by filtration. The recovery rate of the graphite reached 95%.
[0123] (2) The recovered graphite obtained in step (1) is vacuum dried and then leached with citric acid to remove metal impurities therein to obtain high-purity graphite, the citric acid concentration is 0.05 mol / L, the solid-liquid ratio is 1:50 g / mL, 90° C., 40 min, and the metal impurity removal rate reaches 99.5%.
[0124] (3) The high-purity graphite described in step (2) is chemically oxidized to form graphite oxide using an oxidant consisting of concentrated sulfuric acid and potassium permanganate, high-purity graphite: concentrated sulfuric acid: potassium permanganate = 1g: 25mL: 3g. The oxidation reaction is first reacted in an ice-water bath for 90min, and then reacted at a medium temperature of 50°C for 8h to obtain a graphite oxide solution, and then hydrogen peroxide is added until no bubbles are generated, and the solution is allowed to stand and then filtered, and finally washed with deionized water until neutral, and then dried to obtain graphite oxide.
[0125] (4) The graphite oxide described in step (3) was dispersed in water at 240W ultrasonic wave for 30 minutes and then placed in a 300°C tube furnace to prepare graphene. Its Raman spectrum is as follows: Fig.12As shown in the figure, the Raman test results show that the G peak appears at 1582.2 cm -1 At, according to the formula W G =1581.6+11 / (1+n 1.6 ) calculated that the number of graphene layers n is 5.94, approximately 6 layers.
[0126] In this comparative example, the high-temperature pyrolysis spray equipment of Example 1 was replaced with a tubular furnace of the same temperature and atmosphere. Experiments found that no nearly single-layer graphene could be obtained, and the number of graphene layers was 6, indicating that the spray pyrolysis process may be more conducive to the exfoliation of graphene oxide than direct tubular furnace pyrolysis.
[0127] Comparative Example 5
[0128] (1) Cut the negative electrode of the waste lithium-ion battery into 1 cm 2 The size was mixed with triethyl phosphate at a solid-liquid ratio of 1:10 g / mL. The mixed system was stirred magnetically and reacted at 20° C. for 60 minutes. Then, the recovered graphite was separated by filtration. The recovery rate of the graphite reached 95%.
[0129] (2) The recovered graphite obtained in step (1) is vacuum dried and then leached with citric acid to remove metal impurities therein to obtain high-purity graphite, the citric acid concentration is 0.05 mol / L, the solid-liquid ratio is 1:50 g / mL, 90° C., 40 min, and the metal impurity removal rate reaches 99.5%.
[0130] (3) The high-purity graphite described in step (2) is chemically oxidized to form graphite oxide using an oxidant consisting of concentrated sulfuric acid and potassium permanganate, high-purity graphite: concentrated sulfuric acid: potassium permanganate = 1g: 25mL: 3g. The oxidation reaction is first reacted in an ice-water bath for 90min, and then reacted at a medium temperature of 50°C for 8h to obtain a graphite oxide solution, and then hydrogen peroxide is added until no bubbles are generated, and the solution is allowed to stand and then filtered, and finally washed with deionized water until neutral, and then dried to obtain graphite oxide.
[0131] (4) The graphite oxide described in step (3) was dispersed in ammonia water at 240W ultrasonic for 30 minutes and then placed in a 300°C tube furnace to prepare graphene. Its Raman spectrum is as follows Fig.13 As shown in the figure, the Raman test results show that the G peak appears at 1582.8cm -1 At, according to the formula W G =1581.6+11 / (1+1.6n) The number of graphene layers n is calculated to be 3.71, approximately 4 layers.
[0132] According to the experimental results of Comparative Example 5, it can be seen that the number of graphene layers prepared by using ammonia water dispersion and then pyrolysis is closer to a few layers than that directly using a tube furnace in Comparative Example 4, which may be due to the combined effect of chemical and thermal reduction. However, it is still not as good as the high-temperature spray pyrolysis after direct ultrasound in water in the embodiment, which can prepare nearly single-layer graphene by direct high-temperature spray pyrolysis in the embodiment.
[0133] Comparative Example 6
[0134] (1) The purchased flake graphite is chemically oxidized to form graphite oxide using an oxidant consisting of concentrated sulfuric acid and potassium permanganate, where flake graphite: concentrated sulfuric acid: potassium permanganate = 1 g: 25 mL: 3 g. The oxidation reaction is first carried out in an ice-water bath for 90 min, then at a medium temperature of 50° C. for 8 h to obtain a graphite oxide solution, and then hydrogen peroxide is added until no bubbles are generated, the solution is allowed to stand and then filtered, and finally washed with deionized water until neutral, and then dried to obtain graphite oxide.
[0135] (2) The graphite oxide described in step (1) was dispersed in water at 240W ultrasonic for 30 minutes, and then graphene was prepared by high temperature spray pyrolysis at 300°C, with an air inlet temperature of 300°C, a liquid spray rate of 50ml / h, and an air atmosphere. The Raman spectrum of the obtained graphene is as follows: Fig.15 As shown in the figure, the Raman test results show that the G peak appears at 1581.6cm -1 At, according to the formula W G =1581.6+11 / (1+n 1.6 ) calculated that the number of graphene layers n is 33.75, which is approximately 34 layers.
[0136] In this comparative example, commercially available flake graphite is directly used to replace the high-purity graphite separated from the negative electrode material of the lithium-ion battery in Example 1, and graphene is prepared by oxidation, ultrasound and spray pyrolysis. However, it is found that the commercially available flake graphite cannot be used to obtain few-layer graphene by the same method as in Example 1. The FTIR spectrum of the oxidized graphite obtained after the flake graphite is oxidized in step (1) is as follows: Fig.14 As shown, it can be seen that Figure 4(FTIR spectrum of graphite oxide in Example 1) After comparison, it is found that the amount of oxygen functional groups contained in the graphite oxide prepared under the same oxidation conditions by using flake graphite as raw material is less than that by using graphite separated from the negative electrode of waste lithium ion batteries as raw material; and in combination with Example 4, near-monolayer graphene can also be prepared by using expanded graphite as raw material. It can be seen that this may be due to the fact that the graphite separated from the negative electrode material of the lithium ion battery increases the graphite interlayer spacing during the battery charging and discharging process, achieving an interlayer expansion effect similar to that of expanded graphite, making it more conducive to the intercalation reaction of concentrated sulfuric acid, so as to access more oxygen-containing functional groups, and thus facilitating the subsequent ultrasonic exfoliation and spray pyrolysis to prepare few-layer graphene, while the flake graphite may not be expanded itself, and from the measured number of graphene layers, it is not easy to obtain near-monolayer graphene according to the method of the embodiment of the present invention.
[0137] Comparative Example 7
[0138] (1) Cut the negative electrode of the waste lithium-ion battery into 1 cm 2 The size was mixed with triethyl phosphate at a solid-liquid ratio of 1:10 g / mL. The mixed system was stirred magnetically and reacted at 20° C. for 60 minutes. Then, the recovered graphite was separated by filtration. The recovery rate of the graphite reached 95%.
[0139] (2) The recovered graphite obtained in step (1) is vacuum dried and then leached with citric acid to remove metal impurities therein to obtain high-purity graphite, the citric acid concentration is 0.05 mol / L, the solid-liquid ratio is 1:50 g / mL, 90° C., 40 min, and the metal impurity removal rate reaches 99.5%.
[0140] (3) The high-purity graphite described in step (2) is first added with concentrated sulfuric acid according to the ratio of high-purity graphite: concentrated sulfuric acid = 1 g: 25 mL, and then 3 g of potassium permanganate is added after reacting in an ice-water bath for 30 min. The oxidation reaction is first reacted in an ice-water bath for 90 min, and then reacted at a medium temperature of 50° C. for 8 h to obtain a graphite oxide solution, and then hydrogen peroxide is added until no bubbles are generated, and the solution is allowed to stand and then filtered, and finally washed with deionized water until neutral, and then dried to obtain graphite oxide.
[0141] (4) The graphite oxide described in step (3) was dispersed in water at 240W ultrasonic for 30 minutes and then placed in 300°C high temperature spray pyrolysis to prepare graphene. Its Raman spectrum is as follows Fig.17 As shown, the Raman test results show that the G peak appears at 1581.7cm -1 At, according to the formula W G =1581.6+11 / (1+n 1.6 ) calculated that the number of graphene layers n is 16.56, which is approximately 17 layers.
[0142] The other conditions of this comparative example are the same as those of Example 1, except that in the oxidation step (3), the oxidizing agents concentrated sulfuric acid and potassium permanganate are added step by step instead of being added simultaneously as in Example 1. The graphene finally obtained has 17 layers, and few-layer graphene cannot be obtained. The FTIR spectrum of the graphite oxide obtained in step (3) is analyzed, as shown in FIG. Fig.16 As shown, by comparing it with the FTIR spectrum of graphite oxide in Example 1, it is found that the graphite oxide prepared by adding concentrated sulfuric acid and potassium permanganate simultaneously to oxidize graphite has a better degree of oxidation than that prepared by adding them step by step, which also provides a good basis for the subsequent preparation of single-layer or few-layer graphene.
[0143] Comparative Example 8
[0144] (1) Cut the negative electrode of the waste lithium-ion battery into 1 cm 2 The size was mixed with triethyl phosphate at a solid-liquid ratio of 1:10 g / mL. The mixed system was stirred magnetically and reacted at 20° C. for 60 minutes. Then, the recovered graphite was separated by filtration. The recovery rate of the graphite reached 95%.
[0145] (2) The recovered graphite obtained in step (1) is vacuum dried and then leached with citric acid to remove metal impurities therein to obtain high-purity graphite, the citric acid concentration is 0.05 mol / L, the solid-liquid ratio is 1:50 g / mL, 90° C., 40 min, and the metal impurity removal rate reaches 99.5%.
[0146] (3) The high-purity graphite described in step (2) is first added with concentrated sulfuric acid according to the ratio of high-purity graphite: concentrated sulfuric acid = 1 g: 25 mL, and then 3 g of potassium permanganate is added after reacting in an ice-water bath for 30 min. The reaction is then continued in an ice-water bath for 60 min, and then reacted at a medium temperature of 35° C. for 0.5 h. Finally, the reaction is carried out at a high temperature of 95° C. until no bubbles are generated when hydrogen peroxide is added. The product is allowed to stand for filtration, and finally washed with deionized water until it is neutral, and then dried to obtain graphite oxide.
[0147] (4) The graphite oxide described in step (3) was dispersed in water at 240W ultrasonic for 30 minutes and then placed in 300°C high temperature spray pyrolysis to prepare graphene. Its Raman spectrum is as follows Fig.18 As shown in the figure, the Raman test results show that the G peak appears at 1582.1cm -1 At, according to the formula W G =1581.6+11 / (1+n 1.6 ) calculated that the number of graphene layers n is 6.71, approximately 7 layers.
[0148] Comparative Example 9
[0149] (1) Concentrated sulfuric acid was added to the purchased flake graphite according to the ratio of graphite: concentrated sulfuric acid = 1 g: 25 mL, and then 3 g of potassium permanganate was added after reacting in an ice-water bath for 30 min. The oxidation reaction was first reacted in an ice-water bath for 90 min, then reacted at a medium temperature of 35°C for 0.5 h, and finally reacted at a high temperature of 95°C until no bubbles were generated after adding hydrogen peroxide, and then filtered after standing, and finally washed with deionized water until neutral, and then dried to obtain graphite oxide.
[0150] (4) The graphite oxide described in step (3) was dispersed in water at 240W ultrasonic for 30 minutes and then placed in 300°C high temperature spray pyrolysis to prepare graphene. Its Raman spectrum is as follows Fig.19 As shown in the figure, the Raman test results show that the G peak appears at 1581.8cm -1 At, according to the formula W G =1581.6+11 / (1+n 1.6 ) calculated that the number of graphene layers n is 12.09, which is approximately 12 layers.
[0151] Comparative Example 10
[0152] (1) Concentrated sulfuric acid was added to the purchased expanded graphite according to the ratio of graphite: concentrated sulfuric acid = 1 g: 25 mL, and then 3 g of potassium permanganate was added after reacting in an ice-water bath for 30 min. The oxidation reaction was first reacted in an ice-water bath for 90 min, then reacted at a medium temperature of 35°C for 0.5 h, and finally reacted at a high temperature of 95°C until no bubbles were generated after adding hydrogen peroxide, and then filtered after standing, and finally washed with deionized water until neutral, and then dried to obtain oxidized graphite.
[0153] (4) The graphite oxide described in step (3) was dispersed in water at 240W ultrasonic for 30 minutes and then placed in 300°C high temperature spray pyrolysis to prepare graphene. Its Raman spectrum is as follows Fig. 20 As shown, the Raman test results show that the G peak appears at 1582.0 cm -1 At, according to the formula W G =1581.6+11 / (1+n 1.6 ) calculated that the number of graphene layers n is 7.75, approximately 8 layers.
[0154] Comparative Examples 8, 9 and 10 respectively use recycled graphite separated from the negative electrode of a lithium ion battery, commercially available flake graphite and commercially available expanded graphite, and use a low temperature-medium temperature-high temperature oxidation process in which concentrated sulfuric acid and potassium permanganate are added separately as oxidants to prepare oxidized graphite. The other steps are the same as in Example 1. The experimental results show that nearly single-layer graphene cannot be obtained. Graphene with 7 and 8 layers is obtained by using battery recycled graphite and expanded graphite, respectively, while only 12 layers of graphene can be obtained by using flake graphite, which once again shows that the recycled graphite and expanded graphite separated from the negative electrode material of a lithium ion battery do have similar expanded layered structures.
[0155] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing single-layer or few-layer graphene using expanded graphite as raw material, characterized in that: The steps include: (1) oxidizing expanded graphite with an oxidant to form oxidized graphite; the expanded graphite is expanded graphite and / or recycled graphite separated from negative electrode materials of lithium-ion batteries; the oxidant comprises concentrated sulfuric acid and potassium permanganate; the oxidation is specifically: mixing the expanded graphite with a mixed oxidant of concentrated sulfuric acid and potassium permanganate, first reacting at an ice-water bath temperature, and then heating the mixture to a medium temperature of less than or equal to 70° C. to cause an oxidation reaction to obtain oxidized graphite; (2) The graphite oxide is ultrasonically dispersed in a solvent and then subjected to high-temperature spray pyrolysis to prepare a single-layer or few-layer graphene.
2. The method according to claim 1, characterized in that The acquisition of the recycled graphite includes the following steps: soaking the disassembled and separated lithium-ion battery negative electrode material in an organic solvent to obtain waste graphite; acid-washing the waste graphite to remove impurities and drying to obtain the impurity-removed recycled graphite, which is the recycled graphite separated from the lithium-ion battery negative electrode material.
3. The method according to claim 1, characterized in that The lithium-ion battery is a lithium-ion battery whose positive electrode material is one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate.
4. The method according to claim 2, characterized in that The organic solvent is one or more of methanol, ethanol, isopropanol, acetone, N-methylformamide, N-methylpyrrolidone, dimethylacetamide, dimethylformamide, triethyl phosphate, and ionic liquid; and / or, The solid-liquid ratio of the disassembled and separated lithium-ion battery negative electrode material to the organic solvent is 1:10-1:100 g / mL, the soaking temperature is 20-60° C., and the soaking time is 5-60 min; and / or, The impurity removal agent used in the pickling and impurity removal is Lewis acid, preferably one or more of citric acid, formic acid, hydrochloric acid, hydrofluoric acid, and trifluoromethanesulfonic acid; the concentration of the Lewis acid is 0.05-3 mol / L; the solid-liquid ratio of the waste graphite to the Lewis acid is 1:10-1:200 g / mL, the reaction time is 10-90 min, and the temperature is 30-90°C.
5. The method according to claim 1, characterized in that The oxidation in step (1) is as follows: the expanded graphite is mixed with a mixed oxidant of concentrated sulfuric acid and potassium permanganate and reacted at an ice-water bath temperature for 60-180 minutes, and then heated to a medium temperature of 30-70° C. and reacted for 4-10 hours.
6. The method according to claim 1, characterized in that The oxidation in step (1) is as follows: the expanded graphite is mixed with a mixed oxidant of concentrated sulfuric acid and potassium permanganate and reacted at an ice-water bath temperature for 60-90 minutes, and then heated to a medium temperature of 40-60° C. and reacted for 7-9 hours.
7. The method according to claim 5 or 6, characterized in that The usage ratio of the expanded graphite, concentrated sulfuric acid and potassium permanganate is 1g:(15-25)mL:(1-5)g.
8. The method according to claim 1, characterized in that The power of the ultrasonic dispersion in step (2) is 150W-270W; the time of the ultrasonic dispersion is 10-60min.
9. The method according to claim 1, characterized in that The solvent in step (2) is one or more of water, isopropanol, N-methylformamide, methanol and ethanol.
10. The method according to claim 1, characterized in that The high temperature spray pyrolysis in step (2) has a pyrolysis temperature of 100-500°C.
Citation Information
Patent Citations
Method of producing graphene by stripping graphite via time-space-synchronous ultrasonic treatment and ball-milling process
CN107879332A
Ball milling method for producing graphene from nitromethane-intercalated graphite
CN110127679A
Method for preparing graphene by recovering graphite from waste lithium ion battery negative electrode material
CN111384462A
Method for preparing single-layer graphene with high carbon-oxygen ratio
CN102153077A
Preparation method for single-layered graphene oxide
CN102897757A
Cited By
Preparation method of graphite oxide
CN119706829A
